SYNERGISTIC EFFECT OF HYBRIDIZATION ON THE FUNCTIONAL PROPERTIES OF AGMF-MWCNT FILLED HYBRID ELECTRICALLY CONDUCTIVE ADHESIVE - Fadzullah, S.H.S.M.; Adnan, Z.; Omar, G.; Mustafa, Z.; Ismail, I.; Malingam, S.D. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
This article investigates the functional properties of the hybrid electrically conductive adhesive (ECA) with various filler loadings. Based on the literature, one of the main issues with silver-based ECA is that it typically consumes a large filler amount. Therefore, the objective of this study is to minimize the quantity of filler used by hybridizing multiwalled carbon nanotube (MWCNT) with silver micro-flakes within an epoxy binder. The experimental results suggest that there is a decreasing value in the volume resistivity of the hybrid ECA with increasing silver (Ag) filler loading, up to 6 wt.% (11 wt.% in total). However, increasing Ag flakes beyond this limit did not further reduce the volume resistivity, which could be attributed to the indication of critical filler concentration (percolation threshold) has been reached. Meanwhile, a similar trend was observed in the mechanical property of the hybrid ECA, in which there is a significant reduction in the lap shear strength, after the highest value at 12 wt.% has been reached. Such observation suggests that there is a large formation of conductive channels between micro and nano-sized hybrid fillers, simultaneously minimizing the percentage of polymer binder connections. Overall, it can be concluded that the optimum formulation of the hybrid ECA in this study is a combination of 5 wt.% MWCNT with 6 wt.% of Ag flakes, which exhibit acceptable functional properties.